Analisis Kajian Struktural Dan Kearifan Lokal Legenda Suku Melayu - Emasta Evayanti Simanjunta; Rianti Rianti (FKIP, Universitas Palangka Raya, 2023)
The purpose of this research is to reveal and study the structural studies and local wisdom values ​​of the legend of the origin of Surau Gading of the Malay people. The method used in this research is a descriptive qualitative method. The data collection technique used in this research is to use the reading and note technique. In this study, the data were analyzed using descriptive qualitative data analysis which included data reduction, data presentation, and conclusion drawing. Based on the results of the analysis, the legend contains structural studies and local wisdom values. Structural studies and local wisdom are found in the legend of the Malay tribe entitled The Origin of Surau Gading which includes 2 elements, namely intrinsic elements and extrinsic elements. Furthermore, the 2 local wisdoms found in this legend are: religious and reciprocal.